A pore gap coordinated biomimetic super-sensitive sensor, a preparation method and applications thereof
Patent Information
- Application Number
- CN202311036040.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-08-17
AI Technical Summary
本发明孔缝协同的仿生超灵敏传感器兼具导电聚合物多孔材料检测范围广和仿生裂纹结构检测灵敏度高的优点,从而解决现有技术中传感器检测灵敏度不高、检测范围窄、稳定性不高、适用性不强的技术问题
[0023](1)本发明中仿生具体是仿的蝎子腿上的狭缝感受器,仿生的是裂纹结构。该裂纹结构受到蝎子对振动刺激响应的启发,根据蝎子的狭缝感受器仿生制成,可以在微弱载荷下发生形变,从而改变裂纹两壁间的间距,导致裂纹两壁上的导电材料的接触状态改变,使引起材料电阻值发生改变。
Smart Images

Figure CN117168664B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of strain sensor technology, and more specifically, to a biomimetic ultrasensitive sensor with pore-slit collaboration, its fabrication method, and its application. Background Technology
[0002] In recent years, the rapid development of mobile internet and big data has brought unprecedented development opportunities to wearable smart products. The growing market for smart wearable electronic devices has further increased the requirements for the sensitivity, stability, detection range, mechanical properties, and operating environment of flexible sensors, driving the rapid development of flexible pressure-sensitive sensing materials. Compared with fiber or film-type flexible pressure-sensitive sensing materials, foam-type flexible pressure-sensitive sensing materials have attracted widespread attention due to their large detection range, strong applicability, stable resistance switching, and greater elasticity and compressibility. However, traditional foam-type flexible pressure-sensitive sensing materials are difficult to meet the high-sensitivity and high-precision detection needs of high-end fields.
[0003] To address this issue, many researchers have improved the sensitivity of foam-type materials by introducing microstructured ionic soft materials into the functional layers, increasing porosity, reducing elastic modulus, and loading multilayer graphene nanosheets. However, these methods still suffer from complex processes, long preparation cycles, high manufacturing costs, and narrow detection ranges. Therefore, developing a biomimetic ultrasensitive sensor with high sensitivity, wide detection range, high stability, and broad applicability through pore-gap synergy, and its fabrication method, is of significant scientific and practical importance for scientific research, production, and daily life. Summary of the Invention
[0004] This invention provides a pore-slit synergistic biomimetic ultrasensitive sensor and its fabrication method. Inspired by the scorpion's response to vibration stimuli, this invention biomimeticly designs a crack structure based on the scorpion's slit receptors. This crack structure can deform under weak loads, thereby changing the distance between the two crack walls, leading to a change in the contact state of the conductive materials on the crack walls and thus altering the material's resistance. In this invention, the micropores and cracks inside the sensor are interconnected, and the coating is uniformly distributed on the surface. The disconnection and reconnection of the conductive coating on the crack surface allows for rapid changes in the conductive network, resulting in high sensitivity. The conductive filler in the porous structure undergoes breakage and contact during stretching, causing changes in resistance. Furthermore, the porous structure effectively resists crack propagation, significantly improving the stability of the crack sensor. This pore-slit synergistic biomimetic ultrasensitive sensor combines the advantages of the wide detection range of conductive polymer porous materials and the high detection sensitivity of biomimetic crack structures, thus solving the technical problems of low detection sensitivity, narrow detection range, low stability, and limited applicability in existing sensors.
[0005] According to a first aspect of the present invention, a pore-slit co-operation sensor is provided. The sensor is a polymer-based material, the surface of which has a crack structure and the interior has a microporous structure, and the internal micropores and the surface cracks are connected. A functional coating is uniformly distributed on the surface of the polymer-based material. Conductive fillers are dispersed in the polymer-based material and distributed in the functional coating.
[0006] The crack structure is used to deform under load, which changes the distance between the two walls of the crack, resulting in a change in the contact state of the conductive materials on the two walls of the crack, thereby causing a change in the resistance value.
[0007] The conductive filler dispersed in the polymer-based material is used to break and contact during stretching, resulting in a change in resistance, and the microporous structure can effectively resist crack propagation, thereby improving the stability of the sensor.
[0008] Preferably, the crack structure has an arc-shaped, circular, square, linear, triangular, or radial shape.
[0009] Preferably, the arc shape is a spiral shape, and more preferably an Archimedean spiral.
[0010] Preferably, the spiral has 3 to 7 turns.
[0011] Preferably, the width of the crack structure is less than 900 μm and the depth is less than 3 mm.
[0012] According to another aspect of the present invention, a method for fabricating the aperture-slit cooperative sensor described in any one of the claims is provided, comprising the following steps:
[0013] (1) The polymer matrix, conductive filler and particulate template agent are mixed and melt-blended to uniformly disperse the conductive filler and particulate template agent in the polymer matrix. The composite melt is extruded into a molding device with a fixed template to obtain a polymer composite material with a cracked surface.
[0014] (2) The polymer composite material with cracked surface obtained in step (1) is immersed in an extractant to remove particulate template agent, and after drying, a conductive polymer-based porous material with pore structure is obtained.
[0015] (3) Dip or spray the functional coating material onto the surface of the conductive polymer-based porous material with a pore structure obtained in step (2), wherein the functional coating contains conductive filler, thereby obtaining the pore-slit coordinated sensor.
[0016] Preferably, the polymer matrix is one or more of the following: polyolefin polymers, polyester polymers, polyamides, polyimides, block copolymer polymers, rubber polymers, polydimethylsiloxane, styrene thermoplastic elastomers, olefin thermoplastic elastomers, vinyl chloride thermoplastic elastomers, and polyamide thermoplastic elastomers.
[0017] The template agent is any one or a combination of sodium sulfate, sodium chloride, lithium chloride, calcium chloride, magnesium chloride, polyethylene oxide, polyethylene, polylactic acid, polyvinyl chloride, polyacrylonitrile, polyamide, and polycaprolactam.
[0018] Preferably, in step (1), by weight, the polymer matrix is 10-60 parts, the template agent is 10-90 parts, and the conductive filler is less than 30 parts.
[0019] Preferably, the conductive fillers described in steps (1) and (3) are each independently selected from at least one of gold nanoparticles, platinum nanoparticles, silver nanoparticles, copper nanoparticles, aluminum-boron alloys, aluminum-chromium alloys, iron-manganese alloys, aluminum-chromium-yttrium alloys, silver-copper-palladium alloys, carbon nanoparticles, silver nanowires, graphene, carbon nanotubes, carbon black, carbon nanofibers, expanded graphite, and Mxene.
[0020] According to another aspect of the present invention, the application of the aperture-slit cooperative sensor described in any one of the claims is provided as a mechanical sensor;
[0021] Preferably, the mechanical sensor is a water droplet sensor.
[0022] In summary, compared with the prior art, the above-described technical solutions conceived by this invention mainly possess the following technical advantages:
[0023] (1) In this invention, the biomimetic design specifically imitates the slit receptors on a scorpion's leg, and the biomimetic design is a crack structure. This crack structure is inspired by the scorpion's response to vibration stimulation and is biomimetic based on the scorpion's slit receptors. It can deform under weak loads, thereby changing the distance between the two walls of the crack, which leads to a change in the contact state of the conductive materials on the two walls of the crack, causing a change in the material's resistance value.
[0024] (2) The biomimetic ultrasensitive sensor of the present invention, which combines the advantages of wide detection range of conductive polymer porous materials and high detection sensitivity of biomimetic crack structure, has the advantages of wide detection range of conductive polymer porous materials and high detection sensitivity of biomimetic crack structure.
[0025] (3) The biomimetic ultrasensitive sensor structure of the present invention with hole-slit collaboration has controllable performance and can be adapted to specific application scenarios with the help of functional coating. It has the advantages of long service life, strong practicality and high stability.
[0026] (4) The melt-blending process in this invention also includes conductive fillers, and / or the functional coating material contains conductive fillers. The conductive fillers in the melt-blending provide conductivity to the porous structure, while the conductive fillers in the functional coating provide conductivity to the cracked structure. The inclusion of conductive fillers in both the melt-blending and the functional coating is used to improve sensitivity.
[0027] (5) The biomimetic ultrasensitive sensor with hole-slit collaboration is green and pollution-free in its manufacturing process, and is low in cost and simple to operate, making it suitable for industrialization and large-scale production. Attached Figure Description
[0028] Figure 1 This is a flowchart illustrating the fabrication process of the biomimetic ultrasensitive sensor with pore-slit collaboration.
[0029] Figure 2 SEM image of the surface structure of the fabricated biomimetic ultrasensitive sensor.
[0030] Figure 3 SEM image of the cross-section of the fabricated biomimetic ultrasensitive sensor.
[0031] Figure 4 Wetting performance testing of the prepared biomimetic ultrasensitive sensor.
[0032] Figure 5 The dynamic effect of a water droplet falling 5 cm onto the sample surface is shown.
[0033] Figure 6 The time-resistance (ΔR / R0) variation curves and cycle number-resistance (ΔR / R0) variation curves of a biomimetic ultrasensitive sensor with a crack number of 7 co-existing pores are shown for different tensile strains and frequencies.
[0034] Figure 7 The curves show the change in resistance (ΔR / R0) over time as water droplets of the same size fall at different heights, and the curves show the change in resistance (ΔR / R0) over time as water droplets of different sizes fall at the same height.
[0035] Figure 8 The time-resistance (ΔR / R0) variation curves of three comparative examples under different tensile strains at a frequency of 1 Hz are shown. Detailed Implementation
[0036] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0037] The present invention discloses a method for fabricating a biomimetic ultrasensitive sensor with pore-slit collaboration, comprising the following steps:
[0038] S1: The polymer matrix, template agent, and first conductive filler are premixed in a certain mass ratio, with 10-60 parts of polymer, 10-90 parts of template agent, and 0-30 parts of conductive filler by weight. Then, the mixture is added to a mixing and blending equipment for melt blending. The mixture formed by the polymer matrix, template agent, and conductive filler undergoes cyclic stretching and shearing in the mixing and blending equipment. The template agent and conductive filler are uniformly dispersed in the polymer matrix. The composite melt is extruded into a molding equipment with a fixed biomimetic template to prepare a polymer composite material with a cracked structure.
[0039] S2: The polymer composite material with cracked structure is immersed in the extractant to remove the template agent, and then dried to obtain a conductive polymer-based porous material with pore structure.
[0040] S3: A functional coating consisting of an adhesive, a second conductive filler, a solvent, and functional additives is dipped or sprayed onto the surface of a conductive polymer-based porous material with a pore structure to obtain a biomimetic ultrasensitive sensor with pore-slit synergy.
[0041] In some embodiments, the polymer matrix is one or more of the following: thermoplastic polyurethane, epoxy resin, polyethylene, polypropylene, polylactic acid, polyacrylate, polyvinylidene fluoride, polystyrene, polycarbonate, polyamide, polyimide, polyethylene terephthalate, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, styrene-ethylene-butene-styrene block copolymer, styrene-ethylene-propylene-styrene block copolymer, natural rubber, styrene-butadiene rubber, cis-butadiene rubber, isoprene rubber, silicone rubber, chloroprene rubber, butyl rubber, nitrile rubber, ethylene-propylene rubber, fluororubber, polydimethylsiloxane, styrene-based thermoplastic elastomers, olefin-based thermoplastic elastomers, diene-based thermoplastic elastomers, vinyl chloride-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, and thermoplastic vulcanized rubber.
[0042] In some embodiments, the template agent is any one or more combinations of sodium sulfate, sodium chloride, lithium chloride, calcium chloride, magnesium chloride, polyethylene oxide, polyethylene, polylactic acid, polyvinyl chloride, polyacrylonitrile, polyamide, and polycaprolactam.
[0043] In some embodiments, the first conductive filler is any one or more combinations of graphene, carbon nanotubes, carbon black, carbon nanofibers, expanded graphite, Mxene, and silver nanowires.
[0044] In some embodiments, the mixing and compounding equipment is a single-shaft eccentric rotor extruder, a twin-shaft eccentric rotor extruder, a blade extruder, a single-screw extruder, a twin-screw extruder, an eccentric rotor internal mixer, a blade internal mixer, a Brabender internal mixer, or an open mill.
[0045] In some embodiments, the crack morphology is any one or more combinations of arc-shaped, circular, square, straight, triangular, spiral, and radial; the crack width is less than 900 μm, and the crack depth is less than 3 mm.
[0046] In some embodiments, the extractant is any one or more combinations of deionized water, acetic acid, acetone, acetonitrile, benzene, n-butanol, chloroform, cyclohexane, cyclopentane, dichloromethane, dichloroethane, dimethylformamide, dioxane, ethyl acetate, ethanol, diethyl ether, n-heptane, n-hexane, methanol, methyl ethyl ketone, isooctane, pentane, isopropanol, dipropyl ether, tetrachloroethane, tetrahydrofuran, toluene, trichloroethane, and xylene.
[0047] In some embodiments, the adhesive in the functional coating is any one or more combinations of polydimethylsiloxane, polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, vinyl acetate copolymer, polyurethane, polyvinylidene fluoride, sodium carboxymethyl cellulose, polyacrylic acid, sodium polyacrylate, hexafluoropolypropylene, and polyacrylamide; the second conductive filler is any one or more combinations of gold nanoparticles, platinum nanoparticles, silver nanoparticles, copper nanoparticles, aluminum-boron alloy, aluminum-chromium alloy, iron-manganese alloy, aluminum-chromium-yttrium alloy, silver-copper-palladium alloy, carbon nanoparticles, silver nanowires, graphene, carbon nanotubes, carbon black, carbon nanofibers, expanded graphite, and Mxene; the solvent is deionized water, acetic acid, acetone, acetonitrile, etc. The following are any one or more combinations of the following: benzene, n-butanol, chloroform, cyclohexane, cyclopentane, dichloromethane, dichloroethane, dimethylformamide, dioxane, ethyl acetate, ethanol, diethyl ether, n-heptane, n-hexane, methanol, methyl ethyl ketone, isooctane, pentane, isopropanol, dipropyl ether, tetrachloroethane, tetrahydrofuran, toluene, trichloroethane, xylene, polydimethylsiloxane, N,N-dimethylpyrrolidone, and N-methylpyrrolidone; the functional additives are any one or more combinations of the following: hexamethyldisilazane, nano-silica, nano-titanium dioxide, tetramethylcyclotetrasiloxane, polytetrafluoroethylene, chlorinated polyethylene, polyols, zinc oxide and polyvinyl alcohol, zinc glycerol, nano-grade lithium carbonate, nano-grade lithium hydroxide, chlorinated polyethylene, acrylate copolymers, trimethylolpropane, conductive polyaniline, and phthalic anhydride.
[0048] Example 1
[0049] A method for fabricating a biomimetic ultrasensitive sensor with pore-slit collaboration, such as... Figure 1 As shown, it includes the following steps:
[0050] TPU (thermoplastic polyurethane elastomer) was selected as the polymer matrix, anhydrous sodium sulfate as the template agent, and carbon nanotubes as the conductive filler. TPU, anhydrous sodium sulfate, and carbon nanotubes were premixed at a mass ratio of 30:70:1, and then melt-blended in a biaxial eccentric rotor extruder. The processing temperatures of the solid conveying section, melt plasticizing section, melt conveying section, and homogenization metering section of the equipment were 130–230℃, 150–230℃, 160–230℃, and 160–230℃, respectively. The rotor speed for mixing was set to 10–100 rpm. A mixture of TPU, anhydrous sodium sulfate, and carbon nanotubes undergoes cyclic stretching and shearing in a biaxial eccentric rotor extruder. The anhydrous sodium sulfate and carbon nanotubes are uniformly dispersed in the TPU. The composite melt is extruded into a molding device with a fixed biomimetic template to prepare a polymer composite material with a 7-turn Archimedean spiral crack structure. The composite material is 3 cm long and 3 cm wide. The equation of the Archimedean spiral is...
[0051] The polymer composite material with cracked structure was immersed in deionized water for 24 hours to remove the template agent, and then dried for 5-6 hours to obtain a conductive polymer-based porous material with pore structure.
[0052] A functional coating composed of PDMS, graphene, and hexamethyldisilazane is dip-coated or sprayed onto the surface of a conductive polymer-based porous material with a pore-slit structure, thus obtaining a biomimetic ultrasensitive sensor with superhydrophobic properties and pore-slit synergy. The surface structure of the fabricated biomimetic ultrasensitive sensor is as follows: Figure 2 As shown, the functional coating and crack structure of the sensor, along with its side-view SEM image, are presented. It can be seen that the crack structure exhibits an Archimedean spiral morphology, with a depth of 150±5 μm and a width of 30±5 μm. The internal micropores and cracks are interconnected, and the coating is uniformly distributed on the surface. The cross-sectional SEM image of the fabricated biomimetic ultrasensitive sensor is shown below. Figure 3 As shown, the microporous structure inside the sensor is interconnected, and carbon nanotubes are uniformly dispersed in the polymer matrix.
[0053] The wettability of the fabricated pore-slit co-construction biomimetic ultrasensitive sensor was tested, such as... Figure 4 As shown, its contact angle CA = 165 ± 2°, roll-off angle SA = 5 ± 2°, and it exhibits a superhydrophobic wetting state overall. Figure 5 The dynamic effect of a water droplet falling 5 cm onto the sample surface was demonstrated. The water droplet bounced back completely, leaving no residue on the sample surface, indicating that it has a good dynamic stability effect.
[0054] In applications, the fabricated biomimetic ultrasensitive sensor with pore-slit synergy is itself a good mechanical sensor. When the tensile length changes, the resistance changes significantly, and the change in resistance value can accurately represent the amount of change in tensile length. For example... Figure 6 The figures show the time-resistance (ΔR / R0) curves and cycle number-resistance (ΔR / R0) curves of a pore-slit co-located biomimetic ultrasensitive sensor with 7 crack cycles under different tensile strains and frequencies. As shown, the fabricated pore-slit co-located biomimetic ultrasensitive sensor exhibits a significant sensing signal in the tensile deformation range of 0.1% to 1.0%, indicating high sensitivity. The sensor also shows a significant signal in the 0.1Hz to 5Hz range, indicating a short response time. The detection effect remains relatively unchanged with increasing cycle number, demonstrating good stability.
[0055] Furthermore, the fabricated pore-slit coordinated biomimetic ultrasensitive sensor can serve as a sensitive water droplet sensor, reflecting the size of the water droplet or different falling heights through changes in resistance. For example... Figure 7 The image shows the sensing signals (resistance change (ΔR / R0)) of a 70 μL water droplet falling from different heights and the sensing signals (resistance change (ΔR / R0)) of water droplets of different sizes falling from a height of 30 cm. It is evident that the sample outputs significant sensing signals for both water droplets falling from different heights and for water droplets of different sizes.
[0056] Comparative Example 1
[0057] The main difference between this embodiment and Embodiment 1 is that the prepared biomimetic ultrasensitive sensor does not contain a crack structure. Its time-resistance (ΔR / R0) variation curves under different tensile strains at a frequency of 1 Hz are shown below. Figure 8 As shown in Figure a, it can be seen that the resistance change at 0 revolutions is approximately 0.4% to 2.3%, and its sensitivity is not as good as that shown in Example 1.
[0058] Comparative Example 2
[0059] The main difference between this embodiment and Embodiment 1 is that the crack structure of the prepared biomimetic ultrasensitive sensor is a three-turn Archimedean spiral. The composite material has a length of 3 cm, a width of 3 cm, a crack depth of 150 ± 5 μm, and a crack width of 30 ± 5 μm. The equation for the three-turn Archimedean spiral centered at the center of the square composite material is: Its time-resistance (ΔR / R0) variation curves at different tensile strains at a frequency of 1 Hz are as follows: Figure 8 As shown in b, the resistance change after 3 revolutions is approximately 3.0% to 12.5%, and its sensitivity is not as good as that shown in Example 1.
[0060] Comparative Example 3
[0061] The main difference between this embodiment and Embodiment 1 is that the crack structure of the prepared biomimetic ultrasensitive sensor is a 5-turn Archimedean spiral. The composite material is 3 cm long and 3 cm wide. The crack depth is 150 ± 5 μm and the width is 30 ± 5 μm. The equation of the 5-turn Archimedean spiral centered at the center of the square composite material is as follows: Its time-resistance (ΔR / R0) variation curves at different tensile strains at a frequency of 1 Hz are as follows: Figure 8 As shown in c, the resistance change after 5 revolutions is approximately 3.0% to 22.5%, and its sensitivity is not as good as that shown in Example 1.
[0062] The results of the three comparative examples were not as good as those shown in the examples because the effect of hole-crack synergy is enhanced and the sensitivity is continuously improved as the number of cracks increases.
[0063] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A biomimetic ultrasensitive tensile strain sensor with pore-slit synergy, characterized in that, The sensor is a polymer-based composite material. The surface of the polymer-based composite material has a crack structure, and the interior has a microporous structure, with the internal micropores and surface cracks connected. A functional coating is uniformly distributed on the surface of the polymer-based composite material. Conductive fillers are dispersed in the polymer-based composite material, and conductive fillers are distributed in the functional coating. The crack structure has a spiral shape, and the number of spiral turns is 3 to 7. The crack structure is used to deform under load, which changes the distance between the two walls of the crack, resulting in a change in the contact state of the conductive materials on the two walls of the crack, thereby causing a change in the resistance value. The conductive filler dispersed in the polymer-based composite material is used to break and contact during the stretching process, thereby causing a change in resistance, and the microporous structure can effectively resist crack propagation, thereby improving the stability of the sensor. The biomimetic ultrasensitive tensile strain sensor with pore-slit collaboration is prepared through the following steps: (1) The polymer matrix, conductive filler and particulate template agent are mixed and melt-blended to uniformly disperse the conductive filler and particulate template agent in the polymer matrix. The composite melt is extruded into a molding device with a fixed template to obtain a polymer-based material with a cracked surface and conductive filler. (2) The polymer-based material with cracked surface and conductive filler obtained in step (1) is immersed in the extractant to remove the particulate template agent, and after drying, a conductive polymer-based porous material with pore structure is obtained. (3) Dip or spray the functional coating material onto the surface of the conductive polymer-based porous material with pore structure obtained in step (2), wherein the functional coating contains conductive filler to form the polymer-based composite material, thereby obtaining the biomimetic ultrasensitive tensile strain sensor with pore synergy.
2. The biomimetic ultrasensitive tensile strain sensor with pore-slit collaboration as described in claim 1, characterized in that, The crack structure has a width of less than 900 μm and a depth of less than 3 mm.
3. The method for fabricating the biomimetic ultrasensitive tensile strain sensor with pore-slit synergy as described in any one of claims 1-2, characterized in that, Includes the following steps: (1) The polymer matrix, conductive filler and particulate template agent are mixed and melt-blended to uniformly disperse the conductive filler and particulate template agent in the polymer matrix. The composite melt is extruded into a molding device with a fixed template to obtain a polymer-based material with a cracked surface and conductive filler. (2) The polymer-based material with cracked surface and conductive filler obtained in step (1) is immersed in the extractant to remove the particulate template agent, and after drying, a conductive polymer-based porous material with pore structure is obtained. (3) Dip or spray the functional coating material onto the surface of the conductive polymer-based porous material with pore structure obtained in step (2), wherein the functional coating contains conductive filler to form the polymer-based composite material, thereby obtaining the biomimetic ultrasensitive tensile strain sensor with pore synergy.
4. The method for fabricating the biomimetic ultrasensitive tensile strain sensor with pore-slit synergy as described in claim 3, characterized in that, The polymer matrix is one or more of the following: polyolefin polymers, polyester polymers, polyamides, polyimides, block copolymer polymers, rubber polymers, polydimethylsiloxane, styrene thermoplastic elastomers, olefin thermoplastic elastomers, vinyl chloride thermoplastic elastomers, and polyamide thermoplastic elastomers. The template agent is any one or a combination of sodium sulfate, sodium chloride, lithium chloride, calcium chloride, magnesium chloride, polyethylene oxide, polyethylene, polylactic acid, polyvinyl chloride, polyacrylonitrile, polyamide, and polycaprolactam.
5. The method for fabricating a biomimetic ultrasensitive tensile strain sensor with pore-slit synergy as described in claim 3, characterized in that, In step (1), by weight, the polymer matrix is 10-60 parts, the template agent is 10-90 parts, and the conductive filler is less than 30 parts.
6. The method for fabricating a biomimetic ultrasensitive tensile strain sensor with pore-slit synergy as described in claim 3, characterized in that, The conductive fillers described in steps (1) and (3) are each independently selected from at least one of gold nanoparticles, platinum nanoparticles, silver nanoparticles, copper nanoparticles, aluminum-boron alloys, aluminum-chromium alloys, iron-manganese alloys, aluminum-chromium-yttrium alloys, silver-copper-palladium alloys, carbon nanoparticles, silver nanowires, graphene, carbon nanotubes, carbon black, carbon nanofibers, expanded graphite, and Mxene.
7. The application of the pore-slit co-construction biomimetic ultrasensitive tensile strain sensor as described in any one of claims 1-2 as a mechanical sensor.
8. The application as described in claim 7, characterized in that, The mechanical sensor is a water droplet sensor.